Massive Adherent Placenta, Placenta Percreta - Yuliantara, Eric Edwin; Anggraini, Nutria Widya Purna; Prisasanti, Dympna Prameilita (Journal of Maternal and Child Health, 2021)
Background: Adherent placentas including placenta accreta, increta and percreta are conditions where there is abnormal implanta